Du contrôle des connaissances a l'évaluation de la compétence - Bourguignon, Claire (Linguistica (Ljubljana), 2014)
This article shows that research on competence-oriented assessment does not meet the criteria of analytic research but is to be considered as systemic. Indeed, competence-oriented assessment is complex and marks an epistemological turning point in the field of language learning and teaching. It thus upsets the traditional representations based on knowledge assessment. After a presentation of the fundamental concepts of competence-oriented assessment and its impact on language learning and teaching, an explanation is given of why words are not enough to bring about changes in perspective. Teachers will not apply a theoretical framework which does not fit in with their ideas. This is why it seems difficult to envisage any research on competence-oriented assessment without reflecting on how teachers can adapt to a new paradigm.
Keywords: compétence en langue; évaluation; jezikovna zmožnost; ocenjevanje; preverjanje; vérification